2016
DOI: 10.1080/14767058.2016.1174998
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of vaginal birth with mediolateral episiotomy on sexual and pelvic dysfunction and perineal pain

Abstract: Vaginal delivery with mediolateral episiotomy is not associated with urinary and/or fecal incontinence and sexual dysfunction but associated with a decreased sexual functioning as well as sexual desire, arousal and orgasm within postpartum five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 14 publications
2
36
0
6
Order By: Relevance
“…The authors concluded that the CS had no superior effect on postpartum sexual function compared to VD . Although the VD was noted to have a long‐term effect on sexual function in Doğan et al study, such effect was reported to be clinically subtle and did not lead to sexual dysfunction. Similarly, Dabiri et al reported no association between the difference between mode of delivery and postpartum sexual function, there were no statistically significant differences in any of FSFI items.…”
Section: Discussionmentioning
confidence: 92%
“…The authors concluded that the CS had no superior effect on postpartum sexual function compared to VD . Although the VD was noted to have a long‐term effect on sexual function in Doğan et al study, such effect was reported to be clinically subtle and did not lead to sexual dysfunction. Similarly, Dabiri et al reported no association between the difference between mode of delivery and postpartum sexual function, there were no statistically significant differences in any of FSFI items.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors (Doğan et al, 2017) report impact of the episiotomy on sexual desire, arousal and orgasm even 5 years after the birth. On contrary some stud-ies did not found differences in reasuming sexuality postnatally among women with episiotomy or those with intact perineum (Lagana et al, 2015;Kramna and Vrublova, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, dyspareunia rate around 25% was observed in women who had an episiotomy [17]. Sexual disorders in women with postpartum perineal pain have previously been reported [10,18,19]. In addition, a clinical study showed that 12.8% of the women who underwent episiotomy presented chronic perineal pain at 5 months, related to obstetric and postpartum factors ( i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Perineal pain is a common consequence of episiotomy and affects up to 97% of women on day 1 postpartum [5,6], up to 70% of women at day 7 to 10 postpartum [7][8][9] and may persist until at least 5 months postpartum [10,11]. Pain after perineal wound (apart from episiotomy) are also reported but less studied because of the high variability of the localization and the depth of the tear.…”
Section: Introductionmentioning
confidence: 99%